Cytotoxicity difference of 316L stainless steel and titanium reconstruction plate - Ni Putu Mira Sumarta; Coen Pramono Danudiningrat; Ester Arijani Rachmat; Pratiwi Soesilawati (Dental Journal (Majalah Kedokteran Gigi), 2011)
Background: Pure titanium is the most biocompatible material today and used as a gold standard for metallic implants. However, stainless steel is still being used as implants because of its strength, ductility, lower price, corrosion resistant and biocompatibility. Purpose: This study was done to revealed the cytotoxicity difference between reconstruction plate made of 316L stainless steel and of commercially pure (CP) titanium in baby hamster kidney-21 (BHK-21) fibroblast culture through MTT assay. Methods: Eight samples were prepared from reconstruction plates made of stainless steel type 316L grade 2 (Coen’s reconstruction plate®) that had been cut into cylindrical form of 2 mm in diameter and 3 mm long. The other one were made of CP titanium (STEMA Gmbh®)) of 2 mm in diameter and 2,2 mm long; and had been cleaned with silica paper and ultrasonic cleaner, and sterilized in autoclave at 121° C for 20 minutes.9 Both samples were bathed into microplate well containing 50 μl of fibroblast cells with 2 x 105 density in Rosewell Park Memorial Institute-1640 (RPMI-1640) media, spinned at 30 rpm for 5 minutes. Microplate well was incubated for 24 and 48 hours in 37° C. After 24 hours, each well that will be read at 24 hour were added with 50 μl solution containing 5mg/ml MTT reagent in phosphate buffer saline (PBS) solutions, then reincubated for 4 hours in CO2 10% and 37° C. Colorometric assay with MTT was used to evaluate viability of the cells population after 24 hours. Then, each well were added with 50 μl dimethyl sulfoxide (DMSO) and reincubated for 5 minutes in 37° C. the wells were read using Elisa reader in 620 nm wave length. Same steps were done for the wells that will be read in 48 hours. Each data were tabulated and analyzed using independent T-test with significance of 5%. Results: This study showed that the percentage of living fibroblast after exposure to 316L stainless steel reconstruction plate was 61.58% after 24 hours and 62.33% after 48 hours. And after exposure to titanium reconstruction plate, the percentage of living fibroblast was 98.69% after 24 hours and 82.24% after 48 hours. Based on cytotoxicity parameter (CD50%), both reconstruction plate made of 316L stainless steel or titanium showed as a non-toxic materials to fibroblast. Conclusion: Both reconstruction plate made of stainless steel and CP titanium were non-toxic to fibroblast, although the stainless steel plate showed lower cytotoxicity level compared to titanium. Therefore a reconstruction plate made from stainless steel type 316L can be used as a safe material for mandibular reconstruction. Latar belakang: Titanium murni adalah bahan yang paling biokompatibel saat ini dan digunakan sebagai standar emas implan logam. Saat ini stainless steel masih digunakan karena kekuatan, ductility, harganya yang murah, tahan terhadap korosi dan cukup biokompatibel. Tujuan: Penelitian ini dilakukan untuk mengetahui perbedaan sitotoksisitas antara plat rekonstruksi yang terbuat dari titanium murni komersial dan plat rekonstruksi yang terbuat dari stainless steel pada kultur sel fibroblas baby hamster kidney-21 (BHK-21) menggunakan MTT assay. Metode: Delapan sampel yang masing-masing tipe 316L terbuat dari stainless steel 316L grade 2 (Coen’s reconstruction plate®) yang dipotong berbentuk silinder diameter 2 mm dan panjang 3 mm, serta yang terbuat dari titanium murni komersial (STEMA Gmbh®) diameter 2 mm dan panjang 2,2 mm; dan dibersihkan dengan kertas silika dan pembersih ultrasonik serta disterilkan dengan autoclave pada suhu 121° C selama 20 menit. Kedua sampel dimasukkan ke dalam sumur mikroplat yang mengandung 50 μl sel fibroblas dengan kepadatan 2 × 105 dalam media Rosewell Park Memorial Institute-1640 (RPMI-1640), diputar dengan kecepatan 30 rpm selama 5 menit. Sumur mikroplat diinkubasi selama 24 dan 48 jam pada suhu 37° C. Setelah 24 "> jam, pada tiap sumur yang akan dibaca pada jam ke 24 ditambahkan 50 μl cairan yang mengandung 5mg/ml MTT dalam phosphat buffer saline (PBS), kemudian diinkubasi kembali selama 4 jam dalam CO2 10% pada suhu 37° C. Assay kolorimetri dengan MTT digunakan untuk mengetahui viabilitas populasi sel setelah 24 jam. Setiap sumur ditambahkan pelarut dimetil sulfoksida (DMSO) dan diinkubasi kembali selama 5 menit pada suhu 37° C. sumur-sumur tersebut kemudian dibaca dengan Elisa reader dengan panjang gelombang 620 nm. Langkah yang sama dilakukan pada sumur-sumur yang akan dibaca pada jam ke 48. Data kemudian ditabulasi dan dianalisis dengan menggunakan independent T-test dengan signifikansi 5%. Hasil: Penelitian ini menunjukkan presentase fibroblas hidup setelah terpapar plat rekonstruksi yang terbuat dari stainless steel adalah 61,58% setelah 24 jam dan 62,33% setelah 48 jam. Dan setelah paparan dengan plat rekonstruksi yang terbuat dari titanium murni adalah 98,69% setelah 24 jam dan 82,24% setelah 48 jam. Berdasarkan pada parameter sitotoksisitas (CD50%) kedua plat rekonstruksi baik yang terbuat dari titanium murni maupun yang terbuat dari stainless steel tipe 316L merupakan bahan yang tidak bersifat toksik terhadap fibroblas. Kesimpulan: Kedua plat rekonstruksi baik yang terbuat dari stainless steel maupun CP titanium tidak bersifat toksik terhadap fibroblas, walaupun plat stainless steel menunjukkan level sitotoksisitas yang lebih rendah daripada titanium murni. Dengan demikian plat rekonstruksi yang terbuat dari stainless steel 316 L aman digunakan sebagai bahan untuk rekonstruksi mandibula.